Dampak Kinerja Keuangan Terhadap Return Saham - Yosi Kurnia Putri; Herry Goenawan Soedarsa (Jurnal Visi Manajemen, 2025)
By examining “The Impact of Financial Performance on Stock Returns” in cunsomer goods sector manufacturing companies listed on the IDX in 2020”, this research aims to assess the resilience of the company's financial ratios. The historical secondary data applied in this research was obtained from the financial statements of these companies by applying a purposive sampling strategy, which resulted in 30 samples from a total population of 54 companies. The technique applied is multiple linear regression, through the SPSS 20 program. The conclusion of the study describes that “partially, the liquidity ratio has a significant negative effect on stock returns, the solvency ratio has no significant effect, and the profitability ratio has a significant positive effect”.